Pendampingan Program Eco Masjid Untuk Mewujudkan Tempat Ibadah Ramah Lingkungan - Dimas Ali Nafis; Aisyah Aulia; Maulidya Anggraini; Rahmatullah (STAI Ma'had Aly Al-Hikam Malang, 2025)
Abstract This community service activity is a concrete form of community service through structured empowerment programs. One of the problems currently faced by the community is low environmental awareness, including in the management of houses of worship. This program, titled